Agriculture Income Tax in Punjab: Potential Impediments and Policy Suggestions - Chatha, Farooq Azmat (Journal of Pakistan Administration, 2024)
Pakistan faces persistent fiscal deficits, with the federal government struggling to increase revenue. Taxing agricultural income is the responsibility of provincial governments. Despite the potential for substantial revenue, provinces have largely depended on their share of the Federal Consolidated Fund following the Eighteenth Amendment. In Punjab, agricultural income tax remains an underutilized resource. This research explores the barriers to enforcing the Agricultural Income Tax Act 2001 and improving tax collection. Using qualitative methods, including interviews and case studies, the study identifies socio-cultural norms and political influences as significant factors that hinder effective tax collection. These challenges contribute to administrative inefficiencies within revenue authorities. Legal amendments coupled with administrative reforms are crucial to fully realizing the revenue potential of agricultural income tax in Punjab… Pakistan faces fiscal deficits, and the federal government struggles to increase revenue. Agriculture income is taxable by the provincial governments. Post the Eighteenth Amendment, the provinces have mainly relied on their share from the Federal Consolidated Fund and have not diligently tried to increase agricultural income tax collection. There is a need to ascertain the impediments in enforcing the law for optimal tax collection in Punjab. This research is an attempt to fill this gap in the literature. Through a qualitative approach, this paper finds that the issues in the non-implementation of the Agricultural Income Tax Act 2001 in Punjab arise from socio-cultural and political considerations. These are then translated into administrative inefficiencies by the revenue authorities. Legal amendments, as well as administrative reforms, are needed to enhance the revenue collection according to its potential.
Keywords: Agriculture income tax; Punjab Revenue Authority; board of Revenue